United States Code - Congress of the U.S., Washington, DC.; Congress of the U.S., Washington, DC. ([Washington, D.C.] : Govt, 1948)
The document is a copy of Public Law 93-508 enacted by the 93rd Congress, December 3, 1974 to amend title 38, United States Code. Cited as the Vietnam Era Veterans' Readjustment Assistance Act of 1974, it provides for: increased vocational rehabilitation subsistence allowances, educational and training assistance allowances, and special allowances paid to eligible veterans and persons; improved and expanded special programs for educationally disadvantaged veterans and servicemen; improved and expanded veteran-student services program; establishement of an education loan program for veterans and other persons eligibile for benefits; other improvements in the educational benefits; employment of veterans and the wives and widows of certain veterans by improving and expanding the provisions governing the operation of the Veterans Employment Services by increasing the employment of veterans by Federal contractors and subcontractors, and by providing for an action plan for employment of disabled and Vietnam era veterans within the Federal government; and codification and expansion of veterans reemployment rights. (Author/MS)
Microfiche.
Keywords: Educational Legislation; Employment Programs; Federal Legislation; Financial Support; Program Improvement; Veterans; Veterans Education; Vocational Rehabilitation; Vietnam Era Veterans Readjustment Assistance Act; Vietnam Veterans; Legal/Legislative/Regulatory Materials